2020
DOI: 10.1021/acs.energyfuels.0c01231
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Mixing Rules for Bitumen at 1–10 wt % Solvent Dilution When Only Viscosity and Density Are Known

Abstract: Viscosity is an important parameter to assess heavy oil and bitumen upgrading operations, such as bitumen dilution to meet pipeline viscosity specification limits. In conceptual design studies that involve blending of high-and low-viscosity materials, the experimental measurement of viscosity is impractical; therefore, such studies employ mixing rules to estimate mixture viscosity. Mixing rules for conceptual design evaluations where limited or no information apart from the viscosity and density of the bitumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In the literature, various theoretical models are available to predict the viscosity of different mixtures such as suspensions, bitumen–organic solvent mixtures, and water-in-oil (W/O) emulsions. Some of these models were used to correct the measured viscosity of the contaminated bitumen in this study. Their corresponding equations and assumptions based on which these equations are applicable can be found in Section S5 (Tables S4 and S5) of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, various theoretical models are available to predict the viscosity of different mixtures such as suspensions, bitumen–organic solvent mixtures, and water-in-oil (W/O) emulsions. Some of these models were used to correct the measured viscosity of the contaminated bitumen in this study. Their corresponding equations and assumptions based on which these equations are applicable can be found in Section S5 (Tables S4 and S5) of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…For viscosity correction, the mixing rule proposed by Miadonye et al was used in this study. It was reported that for solvent concentrations ranging from 1 to 10 wt %, this mixing rule consistently provided the best viscosity estimation with an absolute average relative deviation (AARD) that varied in the range 0%–35%, depending on the solvent used . In the same study, it was also observed that viscosity overestimation increased with solvent content and that within the uncertainty of the estimation, there was no effect of the chemical nature of the solvent on viscosity prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration of the equipment was verified using a DKD (100 000 BW) certified viscosity standard at atmospheric pressure and temperatures up to 100 °C. Details on the instrument calibration can be found in ref 30.…”
Section: Analysesmentioning
confidence: 99%